Chapter Editors' Introduction - De Vuyst, Sara (Taylor & Francis, 2021)
This edited collection brings together original empirical and theoretical insights into the complex set of relations which exist between age, gender, sexualities and the media in Europe. This book investigates how engagements with media reflect people's constructions and understandings of gender in society, as well as articulations of age in relation to gender and sexuality; the ways in which negotiations of gender and sexuality inform people's practices with media, and not least how mediated representations may reinforce or challenge social hierarchies based in differences of gender, sexual orientation and age. In doing so, it showcases new and innovative research at the forefront of media and communication practice and theory. Including contributions from both established and early career scholars across Europe, it engages with a wide range of hotly debated topics within the context of gender, sexuality and the media, informing academic, public and policy agendas.This collection will be of interest to students and researchers in gender studies, media studies, film and television, cultural studies, sexuality, ageing, sociology and education.